2015
DOI: 10.1111/1541-4337.12163
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Foodborne Viruses in the “Farm to Fork” Chain of Fresh Produce

Abstract: Norovirus (NoV) and hepatitis A virus (HAV) are the most important foodborne viruses. Fresh produce has been identified as an important vehicle for their transmission. In order to supply a basis to identify possible prevention and control strategies, this review intends to demonstrate the fate of foodborne viruses in the farm to fork chain of fresh produce, which include the introduction routes (contamination sources), the viral survival abilities at different stages, and the reactions of foodborne viruses tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 162 publications
0
35
0
Order By: Relevance
“…Foodborne outbreaks caused by enteric viruses linked to irrigation of fresh produce with sewage have been reported (Li et al . ). Noroviruses are frequently present in influent and effluent wastewater (Hewitt et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Foodborne outbreaks caused by enteric viruses linked to irrigation of fresh produce with sewage have been reported (Li et al . ). Noroviruses are frequently present in influent and effluent wastewater (Hewitt et al .…”
Section: Introductionmentioning
confidence: 97%
“…Fresh produce is an important vector for the transmission of foodborne viruses like Norovirus (NoV) and Hepatitis A virus (HAV) to the human host (Li et al 2015). Irrigation water is one of the vehicles identified for the contamination of produce during primary production with pathogenic micro-organisms including viruses (Du Plessis et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leafy greens can be exposed to hNoVs in the field through contaminated seeds, soil, or irrigation water and during harvest through field workers' hands (5). After harvest, the leafy greens are then cooled at the farm or after entering the postharvest processing facility.…”
mentioning
confidence: 99%
“…During the fruit season, berries are manually harvested and consumed as fresh, but also used as dried or frozen ingredients added to many foods. With a minimal use of physical interventions to control the foodborne pathogens, microbial contamination is considered to be the most important food safety issue in berry products (Van Boxstael et al, 2013;Bouwknegt et al, 2015;Li et al, 2015;Jacxsens et al, 2017). In the past decade, the consumption of frozen berries in Europe showed a steep increase (Tavoschi et al, 2015), meanwhile numbers of foodborne outbreaks have been reported.…”
Section: Introductionmentioning
confidence: 99%